2021
DOI: 10.4103/jod.jod_31_21
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Sexual Dysfunction in Women with Diabetes Mellitus

Abstract: Objectives: Female sexual dysfunction (FSD) with chronic diseases such as diabetes has received little attention globally. The aim of this study is to assess the frequency of sexual dysfunction (SD) in women with diabetes; an aspect of female health that has not been explored in our population. Materials and Methods: This cross-sectional observational study using non-probability convenient purposive sampling technique was carried out at three health fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Moreover, regarding the number of living children more than half of them have one to three children and most of them are cesarian. These results agreed with Gerges et al [ 10 ] who studied sexual dysfunction in women with diabetes in Banha and revealed that more than two-thirds of the studied women had from one to three children, in contrast to the result of the current study more than two-thirds of them were delivered with Vaginal delivery mode.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, regarding the number of living children more than half of them have one to three children and most of them are cesarian. These results agreed with Gerges et al [ 10 ] who studied sexual dysfunction in women with diabetes in Banha and revealed that more than two-thirds of the studied women had from one to three children, in contrast to the result of the current study more than two-thirds of them were delivered with Vaginal delivery mode.…”
Section: Discussionsupporting
confidence: 93%
“…Education and counseling are effective in improving women’s sexual function through the provision of knowledge and problem-solving skills. Healthy lifestyles including nutrition, exercise, and sleep by controlling blood sugar levels protect a person from free radicals and indirectly affect their sexual function by regulating the body’s blood flow [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adjustments to diabetes which may be experienced differently could also be a factor. Hence, the variation maybe related to age and duration of diabetes both of which are known mediators of FSD 9,34,37 . Another source of variability could be related to the fact that the FSFI does not specifically exclude sexually inactive women.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the variation maybe related to age and duration of diabetes both of which are known mediators of FSD. 9,34,37 Another source of variability could be related to the fact that the FSFI does not specifically exclude sexually inactive women. While 10 of the included studies excluded sexually inactive women, the prevalence rate in study 10, which did not make it clear whether sexually inactive women were excluded, was 50%.…”
Section: F I G U R E 3 Prevalence Of Female Sexual Dysfunction (Fsd)mentioning
confidence: 99%
“…Education and counseling are effective in improving women's sexual function through the provision of knowledge and problem-solving skills. Healthy lifestyles including nutrition, exercise, and sleep by controlling blood sugar levels protect a person from free radicals and indirectly affect their sexual function by regulating the body's blood ow (Masood, Saeed, Lakho, Masood, Rehman, and Memon, 2021;Sebtain, 2022).…”
Section: Introductionmentioning
confidence: 99%